A Feedback Loop of LINC00665 and the Wnt Signaling Pathway Expedites Osteosarcoma Cell Proliferation, Invasion, and Epithelial‐Mesenchymal Transition. Issue 1 (17th November 2022) - Bai, Jinyu; Zhang, Xiao; Jiang, Fengxian; Shan, Huajian; Gao, Xiang; Bo, Lin; Zhang, Yingzi
Abstract : Objectives: Osteosarcoma (OS) is a malignant tumor with frequent occurrence among teenagers. Long non‐coding RNAs (lncRNAs) play pro‐cancer roles in many tumors. The purpose of this study was to figure out the functional role of a novel lncRNA long intergenic non‐protein coding RNA 665 (LINC00665) in OS by observing the OS cell behaviors. Methods: Quantitative reverse transcription polymerase chain reaction (RT‐qPCR) was used to analyze LINC00665 expression in OS cells. Cell function assays assessed the impacts of LINC00665 on OS cell phenotype. Immunofluorescence and western blot analyzed the function of LINC00665 on epithelial‐mesenchymal transition (EMT) in OS. Moreover, mechanistic assays analyzed the downstream mechanism of LINC00665 in OS cells. Results: LINC00665 was significantly up‐regulated in OS cells. LINC00665 silence facilitated OS cell proliferation, migration, invasion, and EMT while inhibiting cell apoptosis. Mechanically, LINC00665 acted as a competing endogenous RNA (ceRNA) to sponge miR‐1249‐5p and thereby modulated Wnt family member 2B (WNT2B) to activate Wnt pathway. Wnt pathway activated LINC00665 expression transcriptionally. Conclusions: Our study uncovered the cancer‐promoting role of LINC00665 in OS, and the feedback loop of LINC00665/miR‐1249‐5p/WNT2B/Wnt might be a potential target for OS treatment. Abstract : TCF/LEF transcription complex induced the up‐regulation of LINC00665 and LINC00665 promoted OS cell growth. Mechanistically, LINC00665 functioned as a ceRNA to modulate miR‐1249‐5p and thereby up‐regulate WNT2B to enhance the Wnt pathway and the expression of downstream genes, which formed a positive feedback loop.